Seafood Intoxication by Tetrodotoxin: First Case in Europe - Fernández Ortega, Juan Francisco; Morales de los Santos, José M.; Herrera-Gutiérrez, Manuel Enrique; Fernández Sánchez, Victoria Eugenia; Rodríguez Loureo, Paula; Alfonso Rancaño, Amparo; Téllez Andrade, Andrés (Elsevier, 2009)
Background: Tetrodotoxin is considered the most lethal toxin in the marine environment. Prior cases of intoxication previously described correspond to consumption of tetrodotoxin in tropical or subtropical regions of Asia or the Pacific Islands. Objectives: We present the first European case of tetrodotoxin intoxication in a patient who ingested part of a trumpet shellfish (Charonia sauliae) from the Atlantic Ocean in Southern Europe. Case report: Our patient suffered general paralysis, including the respiratory muscles, a few minutes after the consumption of a few grams of C. sauliae. Intubation and mechanical ventilation were necessary for 52 h after the intoxication. The corresponding electrophysiologic studies showed complete non-excitability, with no recordable sensory or motor nerve conduction. We detected the presence of tetrodotoxin in the mollusk and the patient's blood and urine by means of high-performance liquid chromatography-mass spectrometry analysis technique. A previous bioassay showed extremely high quantities of the toxin in the mollusk. Conclusions: This case alerts us to the possibility of a very harmful biotoxin in European coastal waters. This now should be included in the differential diagnosis of similar cases in Europe, and we must be vigilant for its possible presence in Europe.
https://openpolicyfinder.jisc.ac.uk/id/publication/12951
Keywords: Intoxicación por marisco; Tetrodotoxina; Tetrodotoxin poisoning; Mollusk venoms